LOCAL GOVERNMENT'S ROLE IN RAISING TOURISM INCOME: A CASE STUDY IN MASAWAH VILLAGE, PANGANDARAN - Muhammad Gustira Triawan; Dede Sri Kartini; Iyep Saefulrahman; Naufal Rizky Albarkah; Shofi Siti Solihah; Naufaldy Rizkiansyah; Qothrunnada Qothrunnada (INDONESIAN GOVERNANCE JOURNAL : KAJIAN POLITIK-PEMERINTAHAN, 2023)
The tourism sector is used by the Indonesian government because it is considered one of the sources of income, one of which is the Masawah Village, Pangandaran. However, the formulation of policies and their execution to increase income must be appropriate. So, a study was conducted with a descriptive-qualitative method to find out the factual conditions in Masawah Village, Pangandaran. Then, a field study was carried out using an interview method with stakeholders from both the government and the community. This method is considered suitable for use because the data collected is focused on actual problems through the processes of collecting, compiling, processing, and drawing conclusions accompanied by objective results. In this study, it was found that when determining policy goals, attention must be paid to people's aspirations and their needs. Furthermore, it was also found that the utilization of tourism's potential to increase regional income has not been maximized.